Não é sobre o outro, é sobre nós, pessoas negras, anti-epistemicidas: zumbi chegou no campo das epistemologias decoloniais em Biblioteconomia e Ciência da Informação - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia - Universidade Federal do Rio de Janeiro, 2023)
The Black person was a product of an inseparable social and technical machinery of capitalism, of its emergence and globalization. The term "Black" was invented to signify exclusion, dehumanization, and degradation. In the order of Modernity, the Black person had their body transformed into a commodity, and their spirit into merchandise. Using examples within sports, we shed light on the problem of race discussion within the "information field." By examining the cases of Vinicius Jr. and Giannis Antetokounmpo, we propose a counterattack to this dynamic of information regimes that, through the concept of race, constructs the Black being and uses the physical characteristics of these athletes to justify dehumanization and monstrosity, supporting a discourse of power structured in pseudoscience. The analysis of these cases helps us understand the current functioning of discursive logic in the construction of power around certain bodies. From the concept of an information regime, it is possible to analyze the dominant informational mode in a social formation, which defines who the subjects, organizations, rules, and informational authorities are, as well as the preferred means and resources of information, standards of excellence, and models of its organization, interaction, and distribution, while valid at a certain time, place, and circumstance. In this sense, the dissertation gives way to a "lecture," and the discourse gives space to a "manifesto pamphlet" that argues that an image of the zombie created by whites in the transatlantic context served as a tool of control over the enslaved Black bodies. Over time, it was redefined by Black communities themselves, and the characteristics that were once intended to subjugate them were used to frighten their oppressors. It opens a utopian possibility of resistance; the existence of zombies became a myth that instills fear in the masters. This is a research proposal designed to be a "lecture piece," also known as a conference piece, a political and effective approach that adopts the methodology of text writing outlined by a narrative composed of a setting and characters. The choice of this language is due to a subjective crossing that is characteristic of this work since it becomes the alternative found to deal with and combat the painful wound of racism through the poetics of aesthetics and sports. Therefore, the methodology is at a crossroads between art and science, where these poetic writings take on a political dimension to strengthen and highlight their political dimension. In invoking the figure of Frantz Fanon, we call for decoloniality to broaden the perspective and circumvent the hegemonic knowledge reproduced in Library Science and Information Science. Considering the above, we can say that the zombie body is also the body that dribbles, the "deviant body." Deviation, a masculine noun with the negative prefix DES, from Latin VIA, means "path, road." Therefore, the dribbling body is the idea that this body is off the normal path. Thus, the underlying research question, how do we free ourselves from the confinement of a so-called zombie body? is answered with results that point to another counter-colonial concept in Library Science and Information Science. The response to the zombifying conclusions points to the construction of spaces that allow for social mediation where the colonial information regime undergoes a rupture.
Keywords: Zumbi dos Palmares; Pessoas negras; História decolonial do Conhecimento; Peça-Palestra; Zombie; Black People; Decolonial History of Knowledge; Lecture Piece; Ciência da informação